In vivo assessment of the mechanical properties of crystalline lenses in a rabbit model using ultrasound elastography: Effects of ultrasound frequency and age. (July 2019) - Wang, Qingmin; Zhu, Ying; Shao, Meng; Lin, Haoming; Chen, Siping; Chen, Xin; Alizad, Azra; Fatemi, Mostafa; Zhang, Xinyu
Abstract: Purpose: The occurrence of presbyopia and cataract is closely related to changes in the mechanical properties of the crystalline lens. There are no established methods so far for in vivo assessment. By introducing ultrasound elastography, we proposed group velocity (Vg ) of an induced shear wave as a new biomarker to characterize the mechanical properties of the lens in our previous study. Here, we investigated the effect of the ultrasound frequency on measurement accuracy and validated the results with a conventional ex vivo compression testing. We also demonstrated a change trend in Vg and its correlation with age in a rabbit model. Methods: Eight New Zealand white rabbits were fed normally from the fourth to seventh month. An ultrasound elastography system was developed to measure Vg in vivo on every eye once per month. The performances when using a high-frequency (L22-11v) and low-frequency (L11-4v) probe were compared. Rabbits were sacrificed after in vivo measurements by the end of the seventh month and this was followed by ex vivo ultrasound measurements and conventional compression tests on the extracted lenses. Results: The results demonstrated that there were no significance differences in Vg between measurements with high-frequency (USE-HF) and low-frequency (USE-LF) probes in the same month-age group. The mean Vg and the standard deviation of four rabbits that were 7 months old were 2.37 ± 0.24  m/s, 2.36 ± 0.25 m/s, 2.43 ± 0.26 m/s and 2.44 ± 0.38 m/s, with USE-HF for ex vivo and in vivo measurements and USE-LF for ex vivo and in vivo measurements, respectively. There were no significant differences (p > 0.05) and they were all in agreement with the results of compression tests, which was 16.16 ± 1.84 kPa in Young's modulus. The results also showed that Vg increased with age. In combination with the results of our previous study, Vg showed a relatively sharp increase from 2 to 5 months, while it had a slight increase from 5 to 7 months. Conclusions: The USE-HF and USE-LF has comparable accuracy in Vg measurements while USE-HF had an advantage regarding better spatial resolution. The change trend of Vg was in accord with the growth phase of New Zealand white rabbits, which usually results in sexual maturity at 5 months old. This implies that Vg can be used as a biomarker parameter for evaluating the mechanical properties of the lens undergoing physiological changes. Highlights: We introduced ultrasound elastography to evaluate mechanical properties of the lens in our previous study. We proposed the shear wave group velocity as a new biomarker of lens' stiffness. This study was performed on rabbits that were fed normally from the fourth to seventh month. Probes of high and low frequency have similar accuracy on group velocity measurement. Both ex vivo and in vivo measurements with ultrasound elastography are in agreement with the results of conventional mechanical test. Group velocities increased with age, and the trend in changes was consistent with the normal growth phase of the rabbits.